Komunikasi Persuasif dalam Perspektif Hukum untuk Pengembangan Masyarakat Islam di Wilayah Kendal - Rohmah, Siti; Saraya, Sitta (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
Persuasive communication is very important in shaping awareness, attitudes, and behavior, especially in the development of Islamic communities. In Kendal Regency, socio-religious life is influenced not only by culture and tradition, but also by legal regulations that govern social order. This study aims to analyze how persuasive communication from a legal perspective contributes to the sustainable empowerment of Islamic communities. Using a qualitative approach, data was obtained through in-depth interviews, participatory observation, and documentation. The results of the study show that the integration of legal values and Islamic principles strengthens social participation, increases legal awareness, and encourages the formation of an independent and empowered society. This study offers an integrative conceptual model between persuasive communication and legal legitimacy as a humanistic, adaptive, and relevant da'wah strategy in the context of Islamic society at the local level.